Compromiso organizacional en la Municipalidad Distrital San Juan Bautista, año 2025 - Bardales Pereyra, Walter Junior (2025)
This study aimed to determine the level of organizational commitment presented by employees of the San Juan Bautista District Municipality in 2025. The research was descriptive with a quantitative approach, utilizing statistical procedures and data collection techniques to obtain accurate information on the variable under study. The design was non-experimental and correlational, observing phenomena without manipulating variables and relating concepts to each other. The study was cross-sectional, collecting information at a single point in time. The data were processed using IBM SPSS. Among the main results, it was found that 73.3% of respondents had a high level of organizational commitment, demonstrating a strong emotional, normative, and continuity bond with the institution. 26.7% had a fair level, and no cases were recorded at a low level, reflecting a predominantly positive perception of commitment among staff. It is concluded that employees maintain a significant connection with the organization, demonstrating emotional attachment, a sense of responsibility, and a willingness to remain with the organization. This suggests a healthy work environment, conducive to strengthening motivation and retaining talent through appropriate institutional policies.